2023
DOI: 10.1093/nc/niad005
|View full text |Cite
|
Sign up to set email alerts
|

Piecing together the puzzle of emotional consciousness

Abstract: The search for neural correlates of emotional consciousness has gained momentum in the last decades. Nonetheless, disagreements concerning the mechanisms that determine the experiential qualities of emotional consciousness—the “what is it like” to feel an emotion—as well as on their neural correlates have far-reaching consequences on how researchers study and measure emotion, sometimes leading to seemingly irresolvable impasses. The current paper lays out in a balanced way the viewpoint of both cognitive and p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 195 publications
(311 reference statements)
0
0
0
Order By: Relevance
“…In the present study, for the first time, we examined both the subjective and physiological components of emotional intensity, in relation to changes in mutual feeling of connectedness. Although subjective and physiological measures of emotion typically correlate with each other, previous work revealed that the strength of their correlation varies with individual and contextual differences, and that subjective and physiological measures of emotion have partially distinct brain correlates (for a review, see Engelen & Mennella, 2023). In line with this evidence, our results suggest that it is the embodied component of emotional intensity, involving physiological changes, that more closely relates to increased mutual feelings of connectedness, as compared to the conscious experience of arousal.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, for the first time, we examined both the subjective and physiological components of emotional intensity, in relation to changes in mutual feeling of connectedness. Although subjective and physiological measures of emotion typically correlate with each other, previous work revealed that the strength of their correlation varies with individual and contextual differences, and that subjective and physiological measures of emotion have partially distinct brain correlates (for a review, see Engelen & Mennella, 2023). In line with this evidence, our results suggest that it is the embodied component of emotional intensity, involving physiological changes, that more closely relates to increased mutual feelings of connectedness, as compared to the conscious experience of arousal.…”
Section: Discussionmentioning
confidence: 99%